2018
DOI: 10.3390/ijms19061581
|View full text |Cite
|
Sign up to set email alerts
|

Stimulatory Effects of Melatonin on Porcine In Vitro Maturation Are Mediated by MT2 Receptor

Abstract: Melatonin is a multifunctional molecule with numerous biological activities. The fact that melatonin modulates the functions of porcine granulosa cells via the MT2 receptor suggests the possibility of MT2 receptor-mediation for melatonin to promote cumulus expansion of porcine cumulus-oocyte complexes (COCs). Therefore, we investigated the presence of MT2 in porcine COCs, and the effects of melatonin with or without selective MT2 antagonists (luzindole and 4-P-PDOT) on this process; COCs underwent in vitro mat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
28
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(32 citation statements)
references
References 41 publications
4
28
0
Order By: Relevance
“…This result is supported by a study by Ma and Lin et al, who demonstrated a significant decrease in the maturation of mouse oocytes and embryonic development following brusatol treatment [17,46]. In addition, our results are similar to those that were obtained in previous studies [9,10,40] in that melatonin not only increased subsequent embryo development, but also increased the maturation rates of porcine COCs. Moreover, the expression levels of GDF9 and BMP15, which are related to oocyte competence [47], were also significantly influenced in each experimental group.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…This result is supported by a study by Ma and Lin et al, who demonstrated a significant decrease in the maturation of mouse oocytes and embryonic development following brusatol treatment [17,46]. In addition, our results are similar to those that were obtained in previous studies [9,10,40] in that melatonin not only increased subsequent embryo development, but also increased the maturation rates of porcine COCs. Moreover, the expression levels of GDF9 and BMP15, which are related to oocyte competence [47], were also significantly influenced in each experimental group.…”
Section: Discussionsupporting
confidence: 92%
“…Figure 8 shows a schematic of this study. our study shows that melatonin can improve porcine oocyte quality and subsequent embryonic development through its various biological activities [10,40,41]. Melatonin is thought to mediate its effect by binding to receptors on the membrane, i.e., MTs [42], which constitute a superfamily of guanine nucleotide binding protein (G-protein)-coupled receptors [43,44].…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…Melatonin treatment improves cumulus oophorus expansion of porcine COCs during IVM [24], and also increases the first polar body extrusion rate of the oocytes disrupted by heat stress and mono-(2-ethylhexyl) phthalate exposed in the porcine [7,25]. Melatonin participates in modulating functions of granulosa cell through melatonin receptor 2 (MT2), and also promotes cumulus expansion of COCs via MT2 in pigs [26]. Therefore, melatonin treatment can enhance cumulus oophorus expansion and the first polar body extrusion rate of oocytes through melatonin receptors, which is beneficial for nuclear and cytoplasmic maturation of porcine oocytes during IVM.…”
Section: Discussionmentioning
confidence: 99%
“…Melatonin membrane receptors (MT1, MT2) are located in oocytes and granulosa cells (cumulus cells) [58][59][60][61]; it would be of great interest to determine the intracellular signaling pathway by which melatonin promotes oocyte maturation and embryo development. While some reports have examined these intracellular processes of melatonin in oocytes [62][63][64][65], the details remain unclear. It has been reported that melatonin controls the expression of genes related to oocyte maturation including mitochondrial function [53,60,66,67], antioxidative enzymes [53,59,67,68], apoptosis [52,[65][66][67][68][69], cumulus cell expansion [51,61,70], and oocyte maturation factors [61,67].…”
Section: Oocyte Maturation Embryo Development and Melatoninmentioning
confidence: 99%